2019
DOI: 10.3389/fpsyg.2019.02681
|View full text |Cite
|
Sign up to set email alerts
|

Dancers’ Somatic of Musicality

Abstract: Dancers often perform while synchronizing their movements to music, as required by the choreographer. In this article, we introduce the concept of categorizing choreography (or segments of it), according to its relationship with either the rhythm or the melody of the accompanied music, or with both. We demonstrate this distinction through several examples for each category. In a pilot study, we composed choreographic sequences that were either melodic-based or rhythmic-based and taught them to professional dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A second level is embodied attunement, in which the dancers synchronize their movements with sound-energetic characteristics such as melody, harmony, tonality, or timbre, in addition with the beat. In this regard, Marinberg and Aviv [ 47 ] found that in choreographed solo dances, some professional dancers intrinsically tend to move in sync with the rhythm, whereas others move with the melodic phrases of the music. A third level is empathy, which relates to the synchronized bodily articulation with a musical expression–or temporal change of sound-energetic features, termed moving sonic forms–so that the bodily expression is united with the musical expression.…”
Section: Introductionmentioning
confidence: 99%
“…A second level is embodied attunement, in which the dancers synchronize their movements with sound-energetic characteristics such as melody, harmony, tonality, or timbre, in addition with the beat. In this regard, Marinberg and Aviv [ 47 ] found that in choreographed solo dances, some professional dancers intrinsically tend to move in sync with the rhythm, whereas others move with the melodic phrases of the music. A third level is empathy, which relates to the synchronized bodily articulation with a musical expression–or temporal change of sound-energetic features, termed moving sonic forms–so that the bodily expression is united with the musical expression.…”
Section: Introductionmentioning
confidence: 99%